Pengaruh Disiplin Kerja, Lingkungan Kerja, Dan Motivasi Terhadap Kinerja Karyawan Di Bekasi Utara - Diah Indah Lestari; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (JURNAL RISET MANAJEMEN (JURMA), 2024)
The purpose of this research is to investigate how discipline, work environment, and motivation influence employee performance in North Bekasi. This research uses a quantitative approach with a survey method. Data collection was obtained by distributing questionnaires in the form of Google Form. The data used in this research is primary data obtained from first sources or people. The population of this study consisted of 115 respondents who had worked in private companies or government agencies in North Bekasi with an age range of 20 - 50 years. The sample used in this research was 89 people using the Slovin formula. Data collected through questionnaires is measured using a Likert scale with a score of 1 to 5. The data analysis technique in this research uses a Structural Equation Model (SEM) based on Partial Least Square (PLS) with SmartPLS 4.0 software. The results of the research show that work discipline has a significant and positive influence on employee performance, the work environment has a significant and positive influence on employee performance, and motivation has a significant and positive influence on employee performance. The findings of this study have crucial implications for human resource management in terms to increase employee performance.